7α-Hydroxypregnenolone, a New Key Regulator of Locomotor Activity of Vertebrates: Identification, Mode of Action, and Functional Significance - Tsutsui, Kazuyoshi; Haraguchi, Shogo; Matsunaga, Masahiro; Vaudry, Hubert (Frontiers in Endocrinology, 2010)
Steroids synthesized de novo by the central and peripheral nervous systems are called neurosteroids. The formation of neurosteroids from cholesterol in the brain was originally demonstrated in mammals by Baulieu and colleagues. Our studies over the past two decades have also shown that, in birds and amphibians as in mammals, the brain expresses several kinds of steroidogenic enzymes and produces a variety of neurosteroids. Thus, de novo neurosteroidogenesis from cholesterol is a conserved property that occurs throughout vertebrates. However, the biosynthetic pathways of neurosteroids in the brain of vertebrates was considered to be still incompletely elucidated. Recently, 7alpha-hydroxypregnenolone was identified as a novel bioactive neurosteroid stimulating locomotor activity in the brain of newts and quail through activation of the dopaminergic system. Subsequently, diurnal and seasonal changes in synthesis of 7alpha-hydroxypregnenolone in the brain were demonstrated. Interestingly, melatonin derived from the pineal gland and eyes regulates 7alpha-hydroxypregnenolone synthesis in the brain, thus inducing diurnal locomotor changes. Prolactin, an adenohypophyseal hormone, regulates 7alpha-hydroxypregnenolone synthesis in the brain, and may also induce seasonal locomotor changes. This review highlights the identification, mode of action and functional significance of 7alpha-hydroxypregnenolone, a new key regulator of locomotor activity of vertebrates, in terms of diurnal and seasonal changes in 7alpha-hydroxypregnenolone synthesis, and describes some of their regulatory mechanisms.